2016
DOI: 10.1016/j.oooo.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline and tocopherol in the management of cancer patients with medication-related osteonecrosis of the jaw: an observational retrospective study of initial case series

Abstract: Introduction Very few studies have evaluated the efficacy of pentoxifylline and tocopherol (PENT-E) in the management of medication-related osteonecrosis of the jaw (MRONJ), though studies have shown its therapeutic and prophylactic benefit in the management of osteoradionecrosis. We report the outcomes of MRONJ managed with PENT-E in patients with metastatic bone disease/multiple myeloma. Patients and Methods Seven patients diagnosed with refractory established cases of MRONJ due to anti-resorptive medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 31 publications
0
34
0
8
Order By: Relevance
“…27,33 Several studies also reported success with PENTOCLO or associated pentoxifylline-tocopherol in treating ORN in other locations, such as temporal bone or sternum, 29,31 and in cases of drug-related osteonecrosis. 34,35 EBA and initial SOMA score were predictive of success; the two are complementary and well-suited to follow-up of mandibular ORN. Although not identified in the present study, history of tumor resection (associated with mandibular bone resection or not) has been reported as predictive of failure; surgery weakens the operated zone, especially in vascular terms by interrupting the inferior alveolar artery or the facial artery.…”
Section: Secondary Criteriamentioning
confidence: 90%
“…27,33 Several studies also reported success with PENTOCLO or associated pentoxifylline-tocopherol in treating ORN in other locations, such as temporal bone or sternum, 29,31 and in cases of drug-related osteonecrosis. 34,35 EBA and initial SOMA score were predictive of success; the two are complementary and well-suited to follow-up of mandibular ORN. Although not identified in the present study, history of tumor resection (associated with mandibular bone resection or not) has been reported as predictive of failure; surgery weakens the operated zone, especially in vascular terms by interrupting the inferior alveolar artery or the facial artery.…”
Section: Secondary Criteriamentioning
confidence: 90%
“…Currently, there are no fixed protocols or a general consensus for the treatment of MRONJ and treatment is generally aimed at reducing symptoms 11. Depending on the staging of MRONJ, treatment options include chlorhexidine mouthrinses, oral antibiotics, pentoxifylline (which improves peripheral blood flow, decreases fibrosis and reduces inflammation), vitamin E therapy, in addition to more complex options such as hyperbaric oxygen therapy, laser therapy and surgery 12. Cases with stage 3 MRONJ present a therapeutic challenge because of extensive osteonecrosis and infection.…”
Section: Discussionmentioning
confidence: 99%
“…ONJ from osteoporotic patients who underwent yearly zoledronic acid administration and were concomitantly treated with corticosteroids was effectively managed with PTX and tocopherol 20 . In a recent case series, all seven patients suffering from ONJ demonstrated symptom relief, while four patients exhibited bony regeneration of radiolucent defects 21 .…”
Section: Hyun Seo Et Al: the Effects Of Pentoxifylline And Tocophementioning
confidence: 94%